Cardio-cutaneous fistulae—beware the late sternal wound lesion. (21st March 2023) - Ratnaraj, Vignesh; Ivanov, Asen; Buratto, Edward; Skillington, Peter
Abstract: Cardio-cutaneous fistula is a very rare complication of cardiac surgery, and the optimal management strategy is unclear. We present a case of a right ventricle-to-pulmonary artery conduit (RV–PA) forming a cutaneous fistulate that was successfully surgically repaired. A 43-year-old male presented for an elective RV–PA conduit replacement with a cutaneous skin lesion and associated sub-sternal collection. The patient underwent redo-sternotomy for the previous surgical replacement RV–PA conduit, of pulmonary atresia, ventricular septal defect, and ligation of main aorto-pulmonary collateral arteries in childhood, with the subsequent upgrade of the RV–PA conduit using pulmonary homograft. Upon entry into the thoracic cavity, it was clear that there was a direct fistula formed from the RV–PA conduit that was responsible for the skin lesion and hence a direct communication to the PA. We discuss the surgical method and surrounding discussions regarding Cardio-cutaneous fistula in a successful surgical repair when the pathology is difficult to truly identify preoperatively. Abstract : Cardio-cutaneous fistula is a rare complication of cardiac surgery, and the optimal management strategy is unclear.